Criticality: Concept to Enhance the Piezoelectric and Electrocaloric Properties of Ferroelectrics. (5th September 2016) - Weyland, Florian; Acosta, Matias; Koruza, Jurij; Breckner, Patrick; Rödel, Jürgen; Novak, Nikola
Abstract : Compositional engineering with a focus on structural phase transitions has been considered as the most important approach for enhancement of the functional properties of ferroelectric materials due to the critical fluctuation of physical properties. Of special interest are electric‐field‐induced phase transitions, which can terminate in a liquid–vapor‐type critical point with a strong enhancement of functional properties. Whereas the critical point in liquid–vapor space considers changes in temperature and pressure, the critical point in this study is placed in electric field–temperature diagrams. In single crystals, temperature and electric field of a critical point are sharply defined and therefore not appealing for practical applications. However, in ceramics, it is demonstrated that the orientational dependence of the critical point leads to a broadened temperature and electric field range. The presence of a diffuse critical point in ceramics provides a conceptually novel approach for the enhancement of functional properties, such as piezoelectric and electrocaloric (EC) responses, as validated here on the example of the 0.75Bi1/2 Na1/2 TiO3 ‐0.25SrTiO3 lead‐free relaxor ferroelectric ceramics. The realization of a broad criticality range will further facilitate the development of the piezoelectric and EC materials and provide an alternative concept to manipulate the functional properties by application of an electric field. Abstract : The concept of criticality provides an alternative approach to manipulate the functional properties of ferroelectrics by an electric field. The inherent randomness of the grain orientations in polycrystalline samples leads to the existence of a diffuse critical point, resulting in enhanced piezoelectric and electrocaloric properties over a broad temperature and electric field range.